Empirical modelling, simulation, and control of pasteurization process of pink guava puree with fouling - Wan Mohd Fadli Wan Mokhtar
Pasteurization is a very common type of food preservation and is widely used in food industries. Controlling the pasteurization process temperature is the important parameter in pasteurization. However, the disturbances from external environment will deviate the pasteurization process temperature from the desired set point value. In order to control the proses temperature properly, the disturbances must be quickly and efficiently rejected by good control strategy. Hence, dynamic models which relate the distrubances and process need to develop for used in process control system. Therefore, this reseach aims to develop an emperical model of process and distrubances and to investigate the suitable control strategy using conventional proportional integral derivative (PID) controller and advance model predective control (MPC) controller for servo and regulatory problems in pasteurization process of pink guava puree. Temperature of the heating medium was chosen as the manipulated variable to control product temperature whiles the inlet temperature of product and fouling thickness were considered as distyrbances. The research involves two major stages i.e. experimental work to obtain the emperical data and simulation study. The models were estimated using curve fitting technique by MATLAB software. Then, the models were simulated using Simulink and controlled using several types of conventional PID and advance MPC controllers tune by different tuning using methods for both servo and regulatory problems. The obtained models for both process and disturances were represented by first order plus time delay (FOPTD) form with a coefficient of determination (R2) is more than 0.8. Then, these models were successfully validated using new series of experiment data with error less than 6%. Simulation results revealed the minimizing of integral absolute error (IAE) method was satisfactorily adaptable in set point traacking as it resulted in faster settling time, less overshoot and smallest values of integral absolute error when applied in several structures of PID conrollers. Moreover, this tuning method outperforms to reject the disturbance effectively and also very rebust. On the other hand, dynamic matrix control (DMC) algorithm shows superior performance in advanced MPC controller by presenting no overshoot and shorter settling time for both servo and regulatory problems. In additon, MPC controller gives a better performace than PID with less overshoot faster response.